Understanding the role of psychological distance in preventing the spread of kauri dieback - Hugh A. N. Benson; Andrea Grant; Nicole Lindsay; Donald Hine (PLoS ONE, 2025)
Background Kauri dieback is a soil-borne pathogen of the family Phytophthora which is lethal to kauri trees. Despite its risks, residents of New Zealand often do not follow imposed mitigation strategies. In this study we explored the potential impact of three factors on psychological distance to kauri dieback: pro-environmental worldviews, trust in government and physical distance from kauri forests. We also investigated the extent to which previously validated psychological distance measures predicted kauri forest visitors’ compliance with boot-cleaning and trail-usage guidelines (behaviours linked to the spread of kauri dieback). Methods A survey assessing beliefs and behaviours related to kauri dieback was completed by a sample of 451 New Zealand residents who had visited a kauri forest in the past four years. Two path analyses were conducted to determine whether the effects of environmental worldview (NEP score), trust in government, and physical distance on boot cleaning and track use compliance behaviours were mediated by psychological distance. Results Direct effects indicated that higher NEP score and closer physical distance significantly reduced psychological distance, but trust in government did not. Closer psychological distance also significantly improved self-reported track use and boot cleaning behaviours. Indirect effects indicated that psychological distance significantly mediated the effects of worldview, trust and physical distance on boot cleaning and track usage. Several significant direct effects of the exogenous predictors on the compliance behaviours were present after controlling for the mediator, indicative of partial mediation. Conclusions Psychological distance is a reliable predictor of respondents’ boot-cleaning and track-use compliance. Interventions to decrease psychological distance may be beneficial for increasing compliance, although the effects were modest and other potential determinants of compliance also require investigation.